Clinical implications of hypertrophic cardiomyopathy associated with mutations in the alpha-tropomyosin gene. - Yamauchi-Takihara, K. (1996)
OBJECTIVE: The disease-bearing genes for hypertrophic cardiomyopathy (HCM) in HCM families have been identified as the beta-myosin heavy chain, alpha-tropomyosin, and cardiac troponin T genes. Three HCM kindreds with three distinct point mutations in the alpha-tropomyosin gene had extensive clinical evaluations. DESIGN AND RESULTS: Single-strand conformation polymorphism gel analysis of polymerase chain reaction amplified products was used to capture each of the nine exons from the alpha-tropomyosin gene to identify mutations in 60 familial HCM patients. Two missense mutations in exon 2 (Ala63Val and Lys70Thr) and one missense mutation in exon 5 (Asp175Asn) were found in three unrelated HCM kindreds. These kindreds were the subject of clinical, electrocardiographic and echocardiographic studies. The morphological appearance of HCM was similar in the three kindreds. All the patients had severe hypertrophy of the left ventricle with asymmetrical septal hypertrophy during the early stage of the disease, which gradually progressed to dilatation of the left ventricle. Moreover, these kindreds showed similar disease penetrance, age of onset, and incidence of premature sudden death. The disease in these kindreds was severe and resulted in frequent sudden deaths. CONCLUSIONS: Among Japanese patients with familial HCM mutations in the alpha-tropomyosin gene are not as rare as reported, accounting for about 5% of all cases. These mutations are characterised by hypertrophy of the left ventricle which then progresses to dilatation and a high incidence of sudden or disease-related death.